'Appearing the team': from practice to simulation...including commentary by Wahlstrom O, Sathyanarayana TN and D'Avray L - Stephens, John; Abbott-Brailey, Hilary; Platt, Alan; WahlstrÃ¶m, Ola; Sathyanarayana, Tn; DÂ¿Avray, Lynda (International Journal of Therapy & Rehabilitation, 2011)
Background: The growing trend in the development of high fidelity simulation within undergraduate health care education has produced a range of frameworks and guidelines to structure learning opportunities offered through simulation. An attempt to articulate the process of learning through simulation based on clinical practice experience would appear to be a useful step in the development of simulation-practice links in the provision of further options to facilitate students' learning and continuing professional development. Content: The experience of team identity and integration for undergraduate health care students (n=16, adult nursing, physiotherapy, radiography) undertaking their first critical care practice placement is explored and used to underpin a reflective model to inform learning opportunities offered through high fidelity simulation. The analysis of human interaction offered by Erving Goffman through the use of dramaturgical metaphor is applied to frame the key emergent themes of the critical care experience-'observation', fitting in', and 'making a difference'-and shape the developing reflective model. Conclusions: Within the proposed model, the importance of 'space for reflection' and 'meaningful dialogue' within the context, participation, accessibility, and credibility (CPAC) schema are critical aspects that facilitate the integration and development of confidence in task/technical and interpersonal competencies supporting effective clinical outcome.